Islamic Education and Community Development: Building Social Cohesion in Diverse Societies - Lutfia, Lubna (Jurnal Pendidikan Indonesia, 2024)
Background: Religious, ethnic, and cultural diversity presents a serious challenge in building social cohesion in an increasingly pluralistic global society. Islamic education, with a Muslim population of more than 1.8 billion people worldwide, has a strategic position as an agent of social transformation that has great potential in shaping an inclusive and harmonious character. Objective: This study aims to analyze the role of Islamic education in building social cohesion in diverse societies, identify effective institutional models, and develop conceptual models that can be operationalized by practitioners and policymakers. Methods: The study used the Systematic Literature Review (SLR) method with an integrative design referring to the PRISMA 2020 protocol, analyzing 47 selected scientific articles from the Scopus, Web of Science, Google Scholar, and DOAJ databases published between 2020–2025. Results: The study identified six mechanisms of Islamic education's contribution to social cohesion, including the transmission of inclusive values based on wasathiyyah and ukhuwwah, community social capital development, facilitation of dialogue and conflict resolution, economic empowerment, cultivation of moderate identity, and formation of intercultural competence. This research produces an integrative model of ICCD (Islamic Education–Community Cohesion Development) that systematically connects the foundations of Islamic education, supporting institutional factors, community development outcomes, and social cohesion indicators. Implications: These findings imply the need for multicultural value-based curriculum reforms, strengthening educators' intercultural competencies, and educational policies that explicitly integrate the goals of social cohesion in the development of Islamic educational institutions.